3c+d-c=

Simple and best practice solution for 3c+d-c= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3c+d-c= equation:


Simplifying
3c + d + -1c = 0

Reorder the terms:
3c + -1c + d = 0

Combine like terms: 3c + -1c = 2c
2c + d = 0

Solving
2c + d = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-1d' to each side of the equation.
2c + d + -1d = 0 + -1d

Combine like terms: d + -1d = 0
2c + 0 = 0 + -1d
2c = 0 + -1d
Remove the zero:
2c = -1d

Divide each side by '2'.
c = -0.5d

Simplifying
c = -0.5d

See similar equations:

| 3v^2+1v-10=0 | | 16=-9b+2b | | 5d-7=53 | | 38=28-3c | | 2a=54 | | (8-x^3)^(1/3) | | 3ln(6x)=24 | | 9^2-98/7^2*9-9= | | 5/8=-2/5b=1/3b | | 2(5x-10)=9x-18 | | x^2-16x-255=0 | | (1/2)lnx-3=0 | | 6(t)=t+2+3 | | x^2-17x-5184=0 | | 6(-1)=1+2+3 | | 6(1)=1+2+3 | | 6(t)=1+2+3 | | 11465=x^2-25x+65 | | x=2x^2-8x-1 | | 6(t)=[t+2]+3 | | =7(2y-9)-(2y+8) | | y^4-81y^2=0 | | 0.5+0.5b+1=b-3 | | 2+5y=7x+6z | | 2r-4=4b-6r | | 7x+6z=2+5y | | -4y+4y+48= | | 10(6)-7= | | 10x+3y=4 | | 2y^2-6y=10 | | 2/7m-1/7=3/14 | | 14-n=8 |

Equations solver categories